Making the Move: Tips for Externally Hired Department Chairs - Amy Aldridge Sanford; Shawn T. Wahl (Academic Chairpersons Conference Proceedings, 2015)
Many of today’s department chairs are hired as a result of external searches. This roundtable, facilitated by two externally hired chairs, will focus on advantages, challenges, and tips for chairs moving to a new university.
Keywords: External Hire; New Chair; Trust; Challenges; Tips